Bone quality, as measured by trabecular bone score, in patients with primary hyperparathyroidism - Eller-Vainicher, Cristina; Filopanti, Marcello; Palmieri, Serena; Ulivieri, Fabio Massimo; Morelli, Valentina; Zhukouskaya, Volha V; Cairoli, Elisa; Pino, Rosa; Naccarato, Antonella; Verga, Uberta; Scillitani, Alfredo; Beck-Peccoz, Paolo; et al. (European journal of endocrinology, 2013)
ObjectiveIn primary hyperparathyroidism (PHPT), vertebral fractures (VFx) occur regardless of bone mineral density (BMD) and may depend on decreased bone quality. Trabecular bone score (TBS) is a texture measurement acquired during a spinal dual-energy X-ray absorptiometry (DXA). Recently, TBS has been proposed as an index of bone micro-architecture.DesignWe studied 92 PHPT patients (74 females, age 62.1±9.7 years) and 98 control subjects. In all patients at baseline, in 20 surgically treated patients and in 10 conservatively treated patients after 24 months, TBS, spinal (lumbar spine (LS)) and femoral (total hip (TH) and femoral neck (FN)) BMD were assessed by DXA and VFx by spinal radiograph.ResultsPHPT patients had lower TBS (−2.39±1.8) and higher VFx prevalence (43.5%) than controls (−0.98±1.07 and 8.2% respectively, both P<0.0001). TBS was associated with VFx (odds ratio 1.4, 95% CI 1.1–1.9, P=0.02), regardless of LS-BMD, age, BMI and gender, and showed a better compromise between sensitivity (75%) and specificity (61.5%) for detecting VFx than LS-BMD, TH-BMD and FN-BMD (31 and 75%, 72 and 44.2%, and 64 and 65% respectively). In surgically treated patients, TBS, LS-BMD, TH-BMD and FN-BMD increased (+47±44.8,+29.2±34.1,+49.4±48.7 and +30.2±39.3% respectively, all P<0.0001). Among patients treated conservatively, TBS decreased significantly in those (n=3) with incident VFx (−1.3±0.3) compared with those without (−0.01±0.9, P=0.048), while BMD changes were not statistically different (LS 0.3±1.2 vs −0.8±0.9 respectively, P=0.19; TH 0.4±0.8 vs −0.8±1.4 respectively, P=0.13 and FN 0.4±0.9 vs −0.8±1.4 respectively, P=0.14).ConclusionsIn PHPT, bone quality, as measured by TBS, is reduced and associated with VFx and improves after surgery.